The Tramp's Tale: Travels Within the Soviet Union and Across its Borders, 1925–1950. Issue 1 (2nd May 2018) - Fitzpatrick, Sheila
Abstract: Anastasia Egorova was a one-legged Russian tramp whose wanderings took her all over the Soviet Union in the 1920s-1940s. At the end of the Second World War, she decided to see the world, and successfully crossed the Western border in 1945, claiming to be Polish. Travelling on to Italy, she found refuge in a psychiatric hospital and stayed there for four years, until Soviet officials looking for repatriation prospects came by and offered her free passage home. She accepted, and was duly repatriated and returned to her native village in 1950. This microhistory from the Soviet archives is examined with reference to the larger topics of marginality, individual agency, and travel and "self-actualization, " as well as the limitations of the "top-down" totalitarian model for Soviet history and questions of historical subjectivity.